Performance-determining physiological factors in the luge start - Platzer, H. P.; Raschner, C.; Patterson, C. (Journal of Sports Sciences, 2009)
In luge, the start is a performance-determining factor. Athletes spend several months in the off-season training to improve starting performance. The aim of this study was to evaluate the influence of different physiological factors on the luge start and identify an appropriate physiological test battery. Thirteen male members of the Austrian national luge team were recruited. All participants completed a test battery that consisted of tests for balance, jumping, isometric truck flexion and extension strength, leg strength, hand grip strength, isometric bench pull and bench press strength, flexibility, and a luge start simulator. Regression analyses of fitness variables and starting speeds revealed relationships (P at least 0.049) except for flexibility, isometric trunk flexion strength, and isometric leg strength at a knee angle of 100° (P at best 0.069). Results showed that a single variable (isometric bench pull strength) explained most of the variance in maximum push-off speed (R2 = 0.750) and suggest that any test battery should include bench pull, trunk extension, and grip strength tests. Bench pull performance might also be a useful tool in the recruitment of athletes.